Middle East Pain Registry (MEPAIN): Feasibility Study of Chronic Pain Registry and Pilot Phase Results - Zakeri, Habib; Radmehr, Mohammad; Karimi, Aliasghar; Montazeri, Leala; Pedramfard, Pegah; Mahdiyar, Parisa; Hemati, Farnaz; Ebrahimi, Atiyeh; Sadeghi, Sogand; Moalemi, Saba (Galen Medical Journal, 2025)
Background: Chronic pain is a significant public health concern due to its long-term disabling effects. To support systematic data collection and improve patient management, the Middle East Pain Registry (MEPAIN) was developed. This study outlines the registry’s design, evaluates its feasibility, and presents initial findings from its pilot phase. Materials and Methods: MEPAIN was launched on July 21, 2024, with data collected via the Zigorat® software platform through January 22, 2025 for this pilot study. Each patient record included demographic details, pain characteristics (pattern, location, intensity), physical exam findings, imaging results, diagnoses, interventions, and follow-up data. Results: A total of 3,903 patients were registered during the six-month pilot. The cohort was 59.5% female, with a mean age of 53.5 ± 14.8 years; 50.2% were Iranian and 49.5% Omani. Lumbar radiculopathy was the most frequent diagnosis. Osteoarthritis and carpal tunnel syndrome predominated among females, while lumbar radiculopathy and discogenic pain were more common in younger patients. Iranians reported higher pain intensity during exacerbations, while Omanis showed greater prevalence of discogenic pain, spinal stenosis, carpal tunnel syndrome, and failed back surgery syndrome. Paresthesia was the most frequently reported symptom, and transforaminal epidural steroid injection was the most common procedure performed. Conclusion: The MEPAIN registry successfully captures comprehensive clinical and procedural data on patients with chronic pain in the Middle East. It offers a robust platform for clinical evaluation and research, supporting future efforts to tailor pain management strategies in regional populations.